The Effect of Neck-specific Exercise With, or Without a Behavioral Approach, on Pain, Disability, and Self-Efficacy in Chronic Whiplash-associated Disorders. Issue 4 (April 2015) - Ludvigsson, Maria L.; Peterson, Gunnel; O'Leary, Shaun; Dedering, Åsa; Peolsson, Anneli
<x xml:space="preserve">Abstract</x> Objectives: The aim of this study was to compare the effect on self-rated pain, disability, and self-efficacy of 3 interventions for the management of chronic whiplash-associated disorders: physiotherapist-led neck-specific exercise (NSE), physiotherapist-led NSE with the addition of a behavioral approach, or Prescription of Physical Activity (PPA). Materials and Methods: A total of 216 volunteers with chronic whiplash-associated disorders participated in this randomized, assessor blinded, clinical trial of 3 exercise interventions. Self-rated pain/pain bothersomeness (Visual Analogue Scale), disability (Neck Disability Index), and self-efficacy (Self-Efficacy Scale) were evaluated at baseline and at 3 and 6 months. Results: The proportion of patients reaching substantial reduction in pain bothersomness (at least 50% reduction) was more evident (P<0.01) in the 2 NSE groups (29% to 48%) compared with the PPA group (5%) at 3 months. At 6 months 39% to 44% of the patients in the 2 neck-specific groups and 28% in the PPA group reported substantial pain reduction. Reduction of disability was also larger in the 2 neck-specific exercise groups at both 3 and 6 months (P<0.02). Self-efficacy was only improved in the NSE group without a behavioral approach (P=0.02). However, there were no significant differences in any outcomes between the 2 physiotherapist-led NSE groups. Discussion: NSE resulted in superior outcomes compared with PPA in this study, but the observed benefits of adding a behavioral approach to the implementation of exercise in this study were inconclusive.